Effectiveness of testing E6/E7 mRNA and DNA of Human Papilloma Virus in Visual Inspection Acetic acid Positive Women - Parvin, Nilufa; Afrin, Tazeen; Siddikey, Md Al Ahad; Begun, Shamsunnahar (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Several testing tools are used for screening the women for cervical pre-cancer or cancer that are lack in sensitivity, specificity and effectiveness. A range of promising new biomarkers of HPV detection and cancer screening have emerged from the research pipeline, of which HPV DNA and mRNA for oncogenes HPV E6 and E7 are used as molecular evidence of infection and cervical cancer screening. Objective: The objective of the study was to evaluate the effectiveness of Human Papillomavirus (HPV) E6/E7 mRNA and HPV DNA test in Cervical Cancer screening of VIA positive patients. Methodology: This cross-sectional analytical study was carried out in the Department of Obstetrics and Gynecology of SSMC and MH, Dhaka in collaboration with the Department of Virology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka between July 2014 to June 2016 to evaluate HPV E6/E7 mRNA test as an alternative of HPV DNA test for diagnosis of CC among Visual Inspection Acetic acid (VIA) positive women, with an ultimate goal of improving the effectiveness of cervical cancer prevention and treatment. A total of 50 VIA positive were selected for that purpose and tested for HPV DNA test by Hybrid Capture® 2. Test for HPV E6 and E7 mRNA was performed on same samples with real time PCR tests. Results: Among the 50 VIA positive women, 14 (28%) were found positive for HR HPV DNA. On the contrary, 8 (16 %) samples collected from the VIA positive women were positive for HPV E6 or E7 mRNA (any of the two mRNAs. Considering the HPV DNA test as gold standard, the E6/E7 mRNA test showed low sensitivity (57.14 %) but high specificity (100%). On the contrary, in the same way when E6/E7 mRNA was considered as gold standard, the HPV DNA test showed high sensitivity (100 %) and comparatively low specificity (85.71%). In addition, the PPV of HPV mRNA test was 100 % while it was lower for HPV DNA test (75%). On the other hand, the NPV of HPV DNA test was 100 % while 85 % for HPV mRNA test. Conclusion: This study reveals that test for HPV E6/E7 mRNA could help more specifically than HPV DNA test in screening for HPV infection of VIA positive women and along with HPV DNA, this test could give better opportunity for diagnosis of CC. Journal of National Institute of Neurosciences Bangladesh, January 2022; 8(1):73-78